ABORDĂRI METODOLOGICE DE CERCETARE A STĂRII ECOLOGICE A ECOSISTEMELOR URBANE - Mogîldea, Vladimir (CEP USM, 2024)
Urban ecosystems represent mainly human habitats, but usually include significant are as for wild species that are associated with urban habitats. They are socio-ecological systems composed of ecological infrastructure (green and blue) and built infrastructure (grey one). Envi ronmental Infrastructure (EI) provides a wide range of benefits for the population: it reduces air pollution, water pollution, noise pollution, provides protection against floods, droughts and heat waves and maintains a connection between people and nature. Urban ecosystems are considered to be in “good condition” if living conditions for people and urban biodiversity are good. Ano ther criterion refers to the balance within the ecosystem, between built and green infrastructure. The environment quality assessment in urban ecosystems requires a specific methodological ap proach, adapted to the complexity of this ecosystem type. The methodology includes a framework of indicators for assessing the ecological state of urban ecosystems, mapping them to help design or implement policies on urban green infrastruc ture, its biodiversity as well as to measure progress towards international, national, regional or local goals in terms of stability and sustainability of urban ecosystems.
METHODOLOGICAL APPROACHES TO RESEARCH THE ECOLOGICAL STATUS OF URBAN ECOSYSTEMS
MOGÎLDEA, Vladimir. Abordări metodologice de cercetare a stării ecologice a ecosistemelor urbane. In: Integrare prin cercetare și inovare: conferința științifică națională cu participare internațională. Ştiinţe ale naturii și exacte, 9-10 noiembrie 2023. CEP USM, 2024, pp. 222-234. ISBN 978-9975-62-690-3.
Keywords: urban ecosystem; ecological infrastructure; ecosystem services